Valuation of tourists’ willingness to pay for ecological conservation towards a sustainable financial mechanism for national parks: an empirical case of Cuc Phuong National Park, Red River delta, Vietnam - Bui Thi Hoang Lan; Dinh Duc Truong; Le Huy Huan; Nguyen Dieu Hang (Environmental Research Communications)
National Parks (NPs) play an important role in preserving the ecological values of nature, while also bringing economic benefits to the community. However, current NPs in developing countries are facing the challenge of lacking financial resources for conservation goals. This study estimated tourists’ willingness to pay for ecological conservation in Cuc Phuong National Park (CPNP), Vietnam as well as factors affecting willingness to pay. Using dichotomous contingent valuation model and a research sample of 650 randomly selected tourists in Cuc Phuong, the study showed that tourists’ willingness to pay for conservation through additional entry fee was about 47,070 VND in the parametric model and 42,123 VND in the non-parametric model. Factors that influence the probability of accepting payments included income, education level, conservation attitude and awareness of ecological values and travel distance. From there, the study discussed and proposed implications that contribute to mobilizing finance for conservation from the community and financial mechanisms for conservation in NPs in Vietnam and developing countries in Asia.